Study of microleakage at class V cavities prepared by Er : YAG laser using rewetting surface treatment - Lizarelli, RFZ; Silva, PCG; Neto, STP; Bagnato, V. S. (Mary Ann Liebert, Inc., 2004)
Objective: This study was conducted to analyze microleakage in Class V cavity preparation, using rewetting (or not) just after burr or Er:YAG laser preparation of enamel and dentin walls in permanent teeth. Background Data: Several studies reported microleakage around composite restorations when cavity preparation was done or treated by Er:YAG laser. As the hybridized laser is removed when this laser is used to cut dental hard tissue, there is a need for new materials or techniques to minimize gaps and microleakage. Results: Primer solution showed significant effect in enamel and dentin, at the level of 5%, when Er:YAG laser was used as a cutting tool. Using primer solution after phosphoric acid in preparations with the laser, microleakage was similar in degree to when cavities were prepared with the burr. Conclusion: Re-wetting surface just after Er:YAG irradiation and chemical treatment with phosphoric acid using HEMA aqueous solution seems to improve the quality of bioattachment between the adhesive system and enamel/dentin, showing similarities between restoration behaviors independently of the cutting tool, whether burr or laser.